The governance dimensions of food security in the chittagong hill tracts: the case of the ethnic minorities - Alam, Muhammad Shahanoor (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2009.